“Eco-History” and Modern Middle Ages Studies: New Methodological Approaches - L. V. Sofronova; A. V. Khazina (Научный диалог)
Two recent books on the history of the environment and the Middle Ages published by Cambridge University Press are analyzed: Richard Hoffman’s “Ecological History of Medieval Europe” (2014) and Bruce M. S. Campbell’s “The Great Transition: Climate, Disease and Society in the Late Medieval World” (2016). The interdisciplinary approach of both authors is noted, which allowed to re-illuminate such central themes of medieval history as the decline of Rome, religious doctrines, urbanization and technology. It is indicated that the books address key environmental topics: energy use, sustainability, disease and climate change. It is reported that Hoffman and Campbell identify the role of natural forces in such processes as climate change, disease and the transformation of military and political balance. This approach is positively evaluated in this article, as it allows to study the devastating effects of the above factors: hunger, floods, mortality of people and animals, wars and financial crises. It is emphasized that the authors of the analyzed books, immersing medieval history in the context of social ecology, introduce the world of nature into historiography as an acting character (actant) and an object of history itself.